Character Education as An Antidote to Racism Among Generation Z - Rismawati, Rismawati; Muhammad Yahya Muhaimin Syarifuddin; Samudra Sanur, Ilham; Ahmadin, Ahmadin; Aba, Akbar; Khaer , Fajrul (Borneo Novelty Publishing, 2025)
Purpose-This research aims to analyze the role of character education in addressing racism among Generation Z, who are frequently exposed to racial issues through social media. Research Methodology/Design/Approach- A descriptive qualitative approach was used with a library research method. Various relevant literature sources were examined to understand both the phenomenon of racism and strategies for implementing character education. Findings-The study finds that character education—emphasizing values such as tolerance, empathy, justice, and equality—plays a crucial role in fostering an inclusive mindset within Generation Z. These values can be integrated into curricula, extracurricular activities, and digital platforms to support anti-racism efforts. However, challenges such as cultural resistance and unequal access to quality education remain significant obstacles. Addressing these requires collaboration among educators, parents, communities, and social institutions. Originality/value-This research highlights the strategic importance of strengthening character education as a foundation for building an inclusive society free from racial discrimination. It offers insights into integrating anti-racism values within educational programs tailored for the digital era’s unique challenges faced by Generation Z